2011
DOI: 10.1099/mic.0.046235-0
|View full text |Cite
|
Sign up to set email alerts
|

The VarS/VarA two-component system modulates the activity of the Vibrio cholerae quorum-sensing transcriptional regulator HapR

Abstract: The human pathogen Vibrio cholerae uses quorum sensing to regulate the expression of a number of phenotypes, including virulence factor production, in response to changes in cell density. It produces small molecules called autoinducers that increase in concentration as cell density increases, and these autoinducers bind to membrane sensors once they reach a certain threshold. This binding leads to signalling through a downstream phosphorelay pathway to alter the expression of the transcriptional regulator HapR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 34 publications
2
44
3
1
Order By: Relevance
“…A possible explanation for this difference is that the luxC-lacZ fusion used in our study reflects the accumulation of active HapR protein, while previous studies used hapR-lacZ and hapR-GFP promoter and translational fusions (33,48). Recently, it was shown that HapR is additionally regulated at the level of activity (53).…”
Section: Discussionmentioning
confidence: 44%
“…A possible explanation for this difference is that the luxC-lacZ fusion used in our study reflects the accumulation of active HapR protein, while previous studies used hapR-lacZ and hapR-GFP promoter and translational fusions (33,48). Recently, it was shown that HapR is additionally regulated at the level of activity (53).…”
Section: Discussionmentioning
confidence: 44%
“…In V. cholerae, the VarS/VarA system could regulate the expression of CsrB and then control the QS through CsrA, a global regulatory protein (36). The VarS/VarA-CsrA/B/C/D system is involved in the control of HapA expression and biofilm production through HapR in V. cholerae (45,46). In this study, we found that CsrB could be involved in the regulation of the motility in V. alginolyticus, and it predicted the targets of CsrB by sRNA Target (47).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, expression of HapR is regulated at the posttranscriptional level through interactions of hapR mRNA with a number of small RNAs (sRNAs) (140). Recent data indicate an integration of cell density with nutrient availability in quorum sensing (141), raising the possibility that another type of smallmolecule signal may serve as a ligand for HapR. The TFR DarR from M. smegmatis has been shown to interact with cyclic-di-AMP (142), providing a precedent for interactions between TFRs and second messengers.…”
Section: Quorum Sensingmentioning
confidence: 99%